Comparison of Risk of Injury on Artificial Turf and Grass among Young Football Players - Mostafa Zarei; Niloufar Rahmani (Vesnu Publications, 2017)
Introduction: Recently, the use of artificial turf has been increased in many parts of the world. However, the effects of artificial turf on the risk of injuries are still debated in literature and published papers have reported contradictory data. Thus, the aim of this study was to compare the risk of injury on artificial turf and natural grass among young Iranian football players Materials and Methods: In this study, 35 teams (980 players) from the youth league of Iran participated. All soccer-related injuries, number of hours of practice sessions and matches, and type of grass during the study period were reported prospectively by the coaches and medical staff. Injuries which occurred during exercise or matches and due to which the player could not take part in the exercise or match of the following day were recorded. The medical team and coaches of both teams were asked to record the players' injuries in the related form. Results: During the 7 months of the study, 26000 hours of player exposure and 118 soccer-related injuries we recorded. Poisson distribution showed that the overall injury rate on natural grass (4.4 injuries/1000 hours) was significantly lower than the overall injury rate on artificial turf (7.64 injuries/1000 hours) (P < 0.05). Knee (P < 0.05) and ankle injuries incidence rates (P < 0.05) on artificial turf were significantly higher than on natural grass. Overuse injuries on artificial turf were twice that on natural grass (P < 0.05). Conclusion: According to the study results, it is suggested that coaches and young players be more careful about the higher incidence of injuries on artificial grass and measures be taken to prevent injuries on artificial turf.